2003
DOI: 10.1037/0882-7974.18.1.3
|View full text |Cite
|
Sign up to set email alerts
|

The role of self-enhancing evaluations in a successful life transition.

Abstract: The objective of the study was to investigate how self-enhancing evaluations, obtained via positive social comparisons and reflected appraisals, were related to mental health in a later life transition. The sample consisted of 266 women who were interviewed once before and 3 times after the experience of community relocation. Results extended prior findings suggesting the dynamic impact of self-enhancing evaluative processes on psychological well-being and depressive symptoms. Additional analyses showed eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 41 publications
1
42
0
2
Order By: Relevance
“…Particularly the subcomponents of satisfaction with appearance, selfconfidence and self-assurance, abilities and skills, and vitality significantly saturate the overall level of satisfaction with own person in the students of sport sciences. Self-evaluation is a source of life success of an individual, his/her social position and prestige (Kwan, Love, Ryff, & Essen, 2003). Self-image/self-conception is developed on the basis of interaction experience (Hogg, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Particularly the subcomponents of satisfaction with appearance, selfconfidence and self-assurance, abilities and skills, and vitality significantly saturate the overall level of satisfaction with own person in the students of sport sciences. Self-evaluation is a source of life success of an individual, his/her social position and prestige (Kwan, Love, Ryff, & Essen, 2003). Self-image/self-conception is developed on the basis of interaction experience (Hogg, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Las autoevaluaciones positivas se traducen en mayores niveles de felicidad y altruismo, mayor disposición de participar en actividades sociales, mayores probabilidades de alcanzar las metas y menores niveles de depresión (Kwan y otros, 2003). Según algunos estudios, el mecanismo subyacente que vincula el optimismo con el bienestar puede relacionarse con las conexiones neuronales del cerebro humano.…”
Section: La Actitud Y El Bienestarunclassified
“…Indeed, the reverse scenario is equally plausible. That is, a high degree of life satisfaction could be the reason why some older adults are self-enhancing, optimistic, feeling in control, engaging in downward social comparison, and so on (Kwan et al, 2003). The questions that motivated this research did not concern the causal direction of these relationships, but whether they signified one underlying process or many.…”
Section: Limitationsmentioning
confidence: 99%
“…For example, in a prospective study of older women who underwent community relocation, Kwan, Love, Ryff, and Essex (2003) showed that the women who made more self-enhancing social comparisons at the time of relocating reported less depression and greater well-being 6 months later. Similar findings with respect to mood and life satisfaction have been reported in studies that experimentally manipulated older adults' opportunity to self-enhance against a given target for social comparison (Bailis & Chipperfield, 2006;Frieswijk, Buunk, Steverink, & Slaets, 2004 (2005) found, in a sample of older adults, that self-enhancing comparative judgments were prospectively associated with lower odds of hospitalization and greater odds of survival over 6 years.…”
Section: Self-enhancement and Life Satisfactionmentioning
confidence: 99%